DYPHEMIA IN DIDONG JALU ARITA MUDE AND BIAK CACAK: DISFEMIA DALAM DIDONG JALU ARITA MUDE DAN BIAK CACAK - Sediken Tara Munthe; Azman Ismail; Yusri Yusuf; Denny Iskandar; Ramli Ramli (LLDIKTI Wilayah X, 2022)
This study aims to describe the type, function, and linguistic form of dysphemia in Didong Jalu Arita Mude and Biak Cacak. The method used is a descriptive method with a qualitative approach. The technique used is listening, note-taking, and interview techniques. The data of this study are expressions containing dysphemia taken from the video of the performance of Didong Jalu Arita Mude with Biak Cacak. In data collection, 2 respondents participated in the interview and were justified by 2 other respondents. The results showed that in the Didong Jalu poem there were various types, functions and linguistic forms of dysphemia, namely; in the expressions mulaho, naru delahe, lenge mubute beloh gere mera, muperot, silent monkey, etc.